Forecasting the Export Values from Thailand to China by Decomposition Method, Smoothing Method and Box–Jenkins Method - โมลิพันธ์ ธนาภรณ์; บัณฑิตวิไล สมศรี (Thai Journal of Science and Technology, 2021)
This research objective is to find the appropriate forecast model for the export values from Thailand to China. The data is collected by Information and Communication Technology Center, Office of Permanent Secretary Ministry of Commerce, in cooperation with the Thai Customs Department, Ministry of Finance. The monthly data from January 2008 to December 2019, a total of 144 months, is divided into 2 sets. The first set has 132 months, from January 2008 to December 2018, is used to find the forecast models. The second set has 12 months, from January 2019 to December 2019, is used to check the accuracy of the forecast model. The forecast techniques employed in this research are Decomposition method, Smoothing method and Box–Jenkins method, then Mean Square Error (MSE) is used in selecting the appropriate forecasting model and Mean Absolute Percentage Error (MAPE) is used to show the percentage of errors between the actual values and the forecast values. The result shows Triple Exponential Smoothing method is the appropriate forecast method for forecasting the export values from Thailand to China, which the MSE is 7,922,026.37 and the MAPE is 7.6556%